P3 Aortopathy assessment in bicuspid aortic valve disease relatives. (2nd March 2016) - Bissell, MM; Biasiolli, L; Oswal, A; Hess, A; Watkins, H; Neubauer, S; Myerson, SG
Abstract : Background: Bicuspid aortic valve (BAV) is known to be heritable and often shows a concomitant aortopathy which was thought  to also be present in some family members. Little is known about aortic function in such family members. We used advanced aortic cardiovascular magnetic resonance (CMR) and peripheral blood analysis to assess evidence for an underlying aortopathy in family members of bicuspid aortic valve patients. Methods: We prospectively enrolled 253 participants: 57 patients with BAV, 142 of their first degree relatives and 54 healthy volunteers. Participants over 6 years of age underwent CMR, and those under 6 years echocardiography. Advanced aortic assessment included aortic diameters, pulse wave velocity, arterial stiffness, maximum rate of systolic dysfunction (MRSD) and distensibility by CMR, total peripheral resistance (TPR) by vicorder© as well as circulating matrix metalloproteinase (MMP) 2 and 9 from a peripheral blood sample. A subset of 10 family members also underwent comprehensive 4D flow MRI assessment. Results: 12% family members were found to have a BAV. 101 family members with a normal functioning tricuspid aortic valve underwent further CMR assessment. Compared to sex, age and blood-pressure matched healthy volunteers all family members had significantly smaller sinus, ascending and descending aortic diameters (Sinuses: HV 16.8 ± 2.2 vs relatives 15.5 ± 1.9 mm, p < 0.05; STJ: HV 15.1 ± 2.1 vs RELATIVES 13.8 ± 1.8 mm, p < 0.05; AA: HV 15.3 ± 2.2 vs relatives 14.4 ± 2.1 mm, p < 0.05). There was no difference in pulse wave velocity, ascending, proximal and distal descending aortic strain, MRSD and distensibility, TPR as well as circulating MMP2 and MMP9. In the subset of family members undergoing advanced 4D flow MRI assessment, there was no difference in flow angle, rotational flow and wall shear stress compared to healthy volunteers. Conclusion: Family members with (normal) trileaflet aortic valves of patients with a bicuspid aortic valve have normal aortic size and function. These findings point towards the importance of haemodynamic factors rather than an additional haemodynamics-independent mechanisms in bicuspid aortic valve patients' aortopathy.